Suffering in Silence: Reasons Why Victims of Gender-Based Violence in Higher Education Institutions Choose Not to Report Their Victimization - Lungelo Cynthia Mdletshe; Mandisa Samukelisiwe Makhaye (Social Sciences, 2025)
The underreporting of gender-based violence (GBV) in institutions of higher learning can be attributed to a range of causes and has an impact on students’ physical and mental health. Institutions of higher learning have made efforts to eradicate the problem, yet incidences are still on the rise, calling for urgent attention. This paper focuses on the causes of the underreporting of GBV in higher education institutions (HEIs) as a point of reference to understanding the root magnitude of the pandemic in order to devise problem-specific interventions to eradicate GBV in institutions of higher learning. The rational choice theory and cultural acceptance of violence theory guided the analysis of the findings discussed in this paper. The rational choice theory provides insights into why victims choose not to report their victimization. The cultural acceptance of violence theory highlights how cultural norms can normalize and perpetuate GBV, creating barriers for victims to come forward. The findings discussed in this paper emanate from a qualitative study that gathered data using 22 one-on-one interviews with students and one focus group comprising seven supporting staff members from the University of Umvoti. Data were thematically analyzed to address the research objectives. The findings indicate that intimidation and distrust in law enforcement agents and institutions are the main reasons why GBV is underreported. Other factors that may be at play include fear of the perpetrator taking revenge, fear of not being believed, stigma and shame, the patriarchy, reliance on money, and a lack of awareness about GBV. To address these issues, this paper recommends that higher education institutions should uphold the principles of justice, fairness, and transparency in handling GBV cases. Moreover, there should be ongoing facilitation of awareness campaigns on GBV covering issues of consent, gender equality, safety, and reporting and support. When victims of GBV feel supported, they are more likely to trust the institution and report any victimization.